Towards Protection Against Low-Rate Distributed Denial of Service Attacks in Platform-as-a-Service Cloud Services - Silva, Bruno Carneiro da (2018)
Nowadays, the variety of technology to perform daily tasks is abundant and different business and people benefit from this diversity. The more technology evolves, more useful it gets and in contrast, they also become target for malicious users. Cloud Computing is one of the technologies that is being adopted by different companies worldwide throughout the years. Its popularity is essentially due to its characteristics and the way it delivers its services. This Cloud expansion also means that malicious users may try to exploit it, as the research studies presented throughout this work revealed. According to these studies, Denial of Service attack is a type of threat that is always trying to take advantage of Cloud Computing Services. Several companies moved or are moving their services to hosted environments provided by Cloud Service Providers and are using several applications based on those services. The literature on the subject, bring to attention that because of this Cloud adoption expansion, the use of applications increased. Therefore, DoS threats are aiming the Application Layer more and additionally, advanced variations are being used such as Low-Rate Distributed Denial of Service attacks. Some researches are being conducted specifically for the detection and mitigation of this kind of threat and the significant problem found within this DDoS variant, is the difficulty to differentiate malicious traffic from legitimate user traffic. The main goal of this attack is to exploit the communication aspect of the HTTP protocol, sending legitimate traffic with small changes to fill the requests of a server slowly, resulting in almost stopping the access of real users to the server resources during the attack. This kind of attack usually has a small time window duration but in order to be more efficient, it is used within infected computers creating a network of attackers, transforming into a Distributed attack. For this work, the idea to battle Low-Rate Distributed Denial of Service attacks, is to integrate different technologies inside an Hybrid Application where the main goal is to identify and separate malicious traffic from legitimate traffic. First, a study is done to observe the behavior of each type of Low-Rate attack in order to gather specific information related to their characteristics when the attack is executing in real-time. Then, using the Tshark filters, the collection of those packet information is done. The next step is to develop combinations of specific information obtained from the packet filtering and compare them. Finally, each packet is analyzed based on these combinations patterns. A log file is created to store the data gathered after the Entropy calculation in a friendly format. In order to test the efficiency of the application, a Cloud virtual infrastructure was built using OpenNebula Sandbox and Apache Web Server. Two tests were done against the infrastructure, the first test had the objective to verify the effectiveness of the tool proportionally against the Cloud environment created. Based on the results of this test, a second test was proposed to demonstrate how the Hybrid Application works against the attacks performed. The conclusion of the tests presented how the types of Slow-Rate DDoS can be disruptive and also exhibited promising results of the Hybrid Application performance against Low-Rate Distributed Denial of Service attacks. The Hybrid Application was successful in identify each type of Low-Rate DDoS, separate the traffic and generate few false positives in the process. The results are displayed in the form of parameters and graphs.